Emotional Intelligence, Workload, and Cyberloafing on Organizational Commitment and Performance of Teachers at the Pelalawan High School Level - Nyoto; Sudarno; Priyono; Surikin; Renaldo, Nicholas (Journal of Applied Business and Technology, 2023)
Schools as the spearhead of education are required to improve the quality and quantity of learning outcomes. The number of problems in schools certainly cannot be separated from the concern of students, teachers, and education staff in achieving the school's vision and mission. This study aims to analyze the influence of emotional intelligence, workload, and cyberloafing on organizational commitment and performance of Indonesian language teachers at the Pelalawan high school level. The population of this study was all Indonesian language teachers at the high school level in Pelalawan Regency as many as 61 samples. This study used descriptive analysis and PLS Structural Equation Model analysis. The results of this study indicate that emotional intelligence is positively significant to organizational commitment, but not significant to teacher performance. The negative workload variable is not significant to organizational commitment but the positive is not significant to teacher performance. The cyberloafing variable is significantly positive on organizational commitment and not significantly negative on teacher performance.